Mononuclear phenolate diamine zinc hydride complexes and their Reactions with CO2 - Brown,NJ; Harris,JE; Yin,X; Silverwood,I; White,AJP; Kazarian,SG; Hellgardt,K; Shaffer,MSP; Williams,CK (Organometallics, 2014)
The synthesis, characterization, and zinc coordination chemistry of the three proligands 2-tert-butyl-4-[tert-butyl (1)/methoxy (2)/nitro (3)]-6-{[(2′-dimethylaminoethyl)methylamino]methyl}phenol are described. Each of the ligands was reacted with diethylzinc to yield zinc ethyl complexes 4–6; these complexes were subsequently reacted with phenylsilanol to yield zinc siloxide complexes 7–9. Finally, the zinc siloxide complexes were reacted with phenylsilane to produce the three new zinc hydride complexes 10–12. The new complexes 4–12 have been fully characterized by NMR spectroscopy, mass spectrometry, and elemental analyses. The structures of the zinc hydride complexes have been probed using VT-NMR spectroscopy and X-ray diffraction experiments. These data indicate that the complexes exhibit mononuclear structures at 298 K, both in the solid state and in solution (d8-toluene). At 203 K, the NMR signals broaden, consistent with an equilibrium between the mononuclear and dinuclear bis(μ-hydrido) complexes. All three zinc hydride complexes react rapidly and quantitatively with carbon dioxide, at 298 K and 1 bar of pressure over 20 min, to form the new zinc formate complexes 13–15. The zinc formate complexes have been analyzed by NMR spectroscopy and VT-NMR studies, which reveal a temperature-dependent monomer–dimer equilibrium that is dominated by the mononuclear species at 298 K.